(untitled) (Research, Society and Development, 2021)
Temporary crowns are a fundamental part of rehabilitative treatments, essential to maintain the marginal integrity of the tooth preparation, as well as to protect the dentine pulp complex in order to avoid sensitivity, caries and gingival problems. Currently, there are several techniques for its manufacture, based on acrylic resin derivatives and the latest technologies. This work aimed to perform an experimental research with 3 types of techniques in order to verify their advantages and disadvantages, working time, which materials are necessary for their use, and to verify the knowledge of dental surgeons about the most current technologies. We can conclude that all techniques have significant advantages and disadvantages, and that all are useful in the daily routine of the dentist, regardless of how long he or she has been working there, although the most recent technology is still unviable in many offices due to its high cost.